Implementasi Rekam Medik Elektronik: Sebuah Studi Kualitatif - Muh Amin; Winny Setyonugroho; Nur Hidayah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Strategy to improve the quality of hospital services through the Hospital Information System (HIS). HIS that contributes to improving services is Electronic Medical Records (EMR), with the aim of supporting integrated, sustainable, efficient and quality health care. This study explores the experience of EMR users in private Islamic hospital, a qualitative research design with a case study approach. Researchers selected 9 participants and conducted semi-structured interviews using interview guidelines. The phenomenological method approach was used for data analysis. Four themes emerged from the data: success factors, implementation barriers, confidentiality or security and the benefits of using EMR. Human resource support, hardwares, finance, leadership, training and technical support are the success factors for implementing EMR. However, there are implementation obstacles where the system error, the system design is not perfect, not compatible with other systems, lack of computer skills, power failure. Meanwhile, the confidentiality of the EMR must be considered regarding the access rights with the username and password to be able to log in and logout, as well as the EMR security risks. However, all of these provide benefits where the contents of the RM are more complete, business efficiency and communication, strategic benefits, and easy access to information. As soon as the hospital benefits from implementing EMR, the EMR implementation process needs to optimize the involvement and participation of organizational members with strong leadership to create a Hi-Tech Hospital. Managed barriers are a challenge in implementing EMR